Patient Cost Sharing in Low Income Populations - Chandra, Amitabh; Gruber, Jonathan; McKnight, Robin (American Economic Review, 2010)
Economic theory suggests that a natural tool to control medical costs is increased consumer cost sharing for medical care. While such cost sharing reduces “full insurance” (wherein patients are indifferent between falling sick or remaining healthy), a greater reliance on coinsurance and copayments can, in theory, stem patient and provider incentives to engage in moral hazard. These issues are particularly salient for low income populations who are at the center of current efforts to expand coverage (among the uninsured in 2008, 38 percent had incomes below the federal poverty line (FPL), and 52 percent had incomes between 100 and 299 percent of the FPL (Kaiser Commission on Medicaid and the Uninsured 2009)). As insurance is expanded to these groups, it is important to understand how they respond to greater levels of patient cost sharing. On the one hand, smarter plan design could help reduce the fiscal pressures associated with insurance expansion. But on the other, it is also possible that low income recipients are unable to cut back on utilization wisely and, consequently, experience hospitalization “offsets” as a result of greater levels of patient cost sharing. In particular, there remains a concern among many that higher cost sharing on primary care will lead to less effective use of primary care, worse health, and, consequently, higher downstream costs at hospitals (the so-called “offset effects”).